Statistical comparison of Monkeypox infection (MPOX) between North and south America - Marín-Machuca, Olegario (2024)
Monkeypox (mpox) is a virus of the same family as human smallpox, detected in tropical forest regions in May 2022 in the United Kingdom and subsequently in Latin America. The objective of the present investigation was to study, by means of mathematical models, the infectivity of Monkeypox in North America in epidemiological comparison with South America. Data on monkeypox infectivity in both North and South America between the beginning of June 2022 and the end of February 2023 have been taken into account. By performing the pandemic dispersion, it was determined that the mathematical model of estimation is: ; with which the number of people infected with monkeypox in both North and South America was estimated. The mathematical model for estimating the rate of infection with monkeypox in both North and South America was determined: . At the 5% significance level, the variances of the constants (k) of the two models are homogeneous, monkeypox infections in North America and South America have no significant difference; the proportionality constants of the models are equal and there is a "very strong correlation" between time and people infected with monkeypox (mpox).